Revised classification of the Cyanidiophyceae based on plastid genome data with descriptions of the Cavernulicolales ord. nov. and Galdieriales ord. nov. (Rhodophyta) - Park, Seung In; Cho, Chung Hyun; Ciniglia, Claudia; Huang, Tzu-Yen; Liu, Shao-Lun; Bustamante, Danilo E.; Calderon, Martha S.; Mansilla Muñoz, Andres Omar; McDermott, Timothy; Andersen, Robert A.; Yoon, Hwan Su (My University, 2023)
The Cyanidiophyceae, an extremophilic red algal class, is distributed worldwide in extreme environments. Species grow either in acidic hot environments or in dim light conditions (e.g., "cave Cyanidium"). The taxonomy and classification systems are currently based on morphological, eco-physiological, and molecular phylogenetic characters; however, previous phylogenetic results showed hidden diversity of the Cyanidiophyceae and suggested a revision of the classification system. To clarify phylogenetic relationships within this red algal class, we employ a phylogenomic approach based on 15 plastomes (10 new) and 15 mitogenomes (seven new). Our phylogenies show consistent relationships among four lineages (Galdieria, "cave Cyanidium", Cyanidium, and Cyanidioschyzon lineages). Each lineage is distinguished by organellar genome characteristics. The "cave Cyanidium" lineage is a distinct clade that diverged after the Galdieria clade but within a larger monophyletic clade that included the Cyanidium and Cyanidioschyzon lineages. Because the "cave Cyanidium" lineage is a mesophilic lineage that differs substantially from the other three thermoacidophilic lineages, we describe it as a new order (Cavernulicolales). Based on this evidence, we reclassified the Cyanidiophyceae into four orders: Cyanidiales, Cyanidioschyzonales, Cavernulicolales ord. nov., and Galdieriales ord. nov. The genetic distance among these four orders is comparable to, or greater than, the distances found between other red algal orders and subclasses. Three new genera (Cavernulicola, Gronococcus, Sciadococcus), five new species (Galdieria javensis, Galdieria phlegrea, Galdieria yellowstonensis, Gronococcus sybilensis, Sciadococcus taiwanensis), and a new nomenclatural combination (Cavernulicola chilensis) are proposed.
Keywords: cave cyanidium; cyanidiales; organelle genome; phylogeny; rhodophyta; taxonomy